Modulation of auditory processing by cortico-cortical feed-forward and feedback projections - Tang, Jie (National Academy of Sciences, 2008)
The auditory center in the cerebrum, the auditory cortex, consists of multiple interconnected areas. The functional role of these interconnections is poorly understood. The auditory cortex of the mustached bat consists of at least nine areas, including the frequency modulation–frequency modulation (FF) and dorsal fringe (DF) areas. The FF and DF areas consist of neurons tuned to specific echo delays carrying target-distance information. The DF area is hierarchically at a higher level than the FF area. Here, we show that the feedback projection from the DF area to the FF area shifts the delay-tuning of FF neurons toward that of the stimulated DF neurons. In contrast, the feed-forward projection from the FF area to the DF area shifts the delay-tuning of DF neurons away from that of the stimulated FF neurons. The lateral projection within the DF area shifts the delay-tuning of DF neurons toward that of the stimulated DF neurons. In contrast, the lateral projection within the FF area shifts the delay-tuning of FF neurons away from that of the stimulated FF neurons. The delay-tuning shift evoked by the DF stimulation was 2.5 times larger than that evoked by the FF stimulation. Our data indicate that the FF–DF feed-forward and FF–FF lateral projections shape the highly selective neural representation of the tuning of the excited DF neurons, whereas the DF–FF feedback and DF–DF lateral projections enhance the representation of the selected tuning, perhaps, for focal processing of information carried by the excited FF neurons.